Identification of predisposing factors and medical conditions associated with the type 2 diabetes mellitus in Bengali males - Begum, Farzana; Shamim, Khondker Manzare; Nazma, Nandita; Khairuzzaman, AKM (Northern International Medical College Journal, 2015)
Background : Recent World Health Organization (WHO) report on diabetes prevalence has alarmed that diabetes has posed a serious threat to the entire population of the world. The prevalence of diabetes for all age groups world wide was estimated to be 2.8% in 2000 and projected to 4.4% in 2030. The number of diabetic population was estimated to rise from 171 million in 2000 to 366 million in 2030. According to the recent report, the highest relative increase will occur in the Middle East, Sub-Sahara, Africa and India. Objective : To identify the predisposing factors and medical conditions associated with type 2 diabetes mellitus in Bengali males. Methodology : It was a descriptive cross-sectional study carried out in the Health Education department of BIRDEM. Fifty males were selected by systematic sampling associated medical conditions were recorded from history on diagnosis and present status during data collection. Data was collected by face to face interview using questionnaire. Data analysed by SPSS version 15. Result : Thirty patients (60%) were 45 years or above at diagnosis. Thirty nine patients (78%) gave the positive family history. Twenty (40%) was father and 19 (38%) mother was affected. The other general predisposing factors included overeating (58%), smoking (50%) and predilection for sweet food (48%), habitual physical inactivity (22%) and body mass index (BMI) consistent with obesity was 6% cases. No patients were alcoholic. History of medication was not very remarkable. Only 4 (8%) gave the history of taking glucocorticoid. At diagnosis from history associated medical conditions were, high cholesterol level in 10% and hypertension in 8% cases while taking data they were found with Coronary artery disease 10%, fatty liver 2%, high cholesterol 16%, hypertension 10%. Where as cerebrovuscular disease, chronic pancreatitis, recurrent urinary and genital tract infection or previously identified impaired glucose intolerance was not reported in any patients. Conclusion : Overeating, smokings, predilection for sweet food are the predisposing factors of type 2 diabetes mellitus in present study. Hypercholesterolaemia, hypertension, coronary artery disease, recurrent skin infections were associated medical conditions. Northern International Medical College Journal Vol.6(2) 2015: 68-69